The debate continues – What is the role of MCU and mitochondrial calcium uptake in the heart?. (June 2020) - Garbincius, Joanne F.; Luongo, Timothy S.; Elrod, John W.
Abstract: Since the identification of the mitochondrial calcium uniporter (MCU) in 2011, several studies utilizing genetic models have attempted to decipher the role of mitochondrial calcium uptake in cardiac physiology. Confounding results in various mutant mouse models have led to an ongoing debate regarding the function of MCU in the heart. In this review, we evaluate and discuss the totality of evidence for mitochondrial calcium uptake in the cardiac stress response and highlight recent reports that implicate MCU in the control of homeostatic cardiac metabolism and function. This review concludes with a discussion of current gaps in knowledge and remaining experiments to define how MCU contributes to contractile function, cell death, metabolic regulation, and heart failure progression. Highlights: MCU is required to support increased cardiac contractility during sympathetic stimulation. New data suggest MCU-dependent m Ca 2+ uptake also supports basal cardiac function. Acute MCU disruption protects against cardiac I/R injury. The heart has robust compensatory mechanisms to adapt to chronic MCU disruption. MCU-independent pathways may mediate m Ca 2+ uptake during sustained stress.